2017
DOI: 10.1038/s41598-017-05515-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging mass spectrometry and MS/MS molecular networking reveals chemical interactions among cuticular bacteria and pathogenic fungi associated with fungus-growing ants

Abstract: The fungus-growing ant-microbe symbiosis is an ideal system to study chemistry-based microbial interactions due to the wealth of microbial interactions described, and the lack of information on the molecules involved therein. In this study, we employed a combination of MALDI imaging mass spectrometry (MALDI-IMS) and MS/MS molecular networking to study chemistry-based microbial interactions in this system. MALDI IMS was used to visualize the distribution of antimicrobials at the inhibition zone between bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 103 publications
2
48
0
Order By: Relevance
“…The finding of shearinines is in line with Boya et al., who recently observed shearinines D, F, and J in a co‐cultivation experiment with mutualistic Streptomyces symbionts of Acromyrmex echinatior leaf‐cutting ants against E. weberi TZ49 . Also, genome mining using antismash revealed that the E. weberi genome comprises genes involved in indole terpenoid biosynthesis fitting to the formation of shearinines.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The finding of shearinines is in line with Boya et al., who recently observed shearinines D, F, and J in a co‐cultivation experiment with mutualistic Streptomyces symbionts of Acromyrmex echinatior leaf‐cutting ants against E. weberi TZ49 . Also, genome mining using antismash revealed that the E. weberi genome comprises genes involved in indole terpenoid biosynthesis fitting to the formation of shearinines.…”
Section: Discussionsupporting
confidence: 88%
“…Several shearinines have been recently identified as secondary metabolites from E. weberi . However, we observed additional prominent peaks 1 and 2 in the LC‐DAD‐ESI‐MS profile that turned out to be novel shearinine derivatives.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The families of nitrogen-fixing bacteria (NFB) consist of more than one hundred of prokaryotes (Semenov et al, 2016). Generally, the symbiotic relationship between NFB and its host belongs to one-to-many relationship (Boya P et al, 2017). The initial product of assimilation with carbon dioxide is malic acid or aspartic acid in symbiotic NFB related to C4 plants, which the fixation efficiency was higher than that in C3 plant with the 3-phosphoglyceric acid.…”
Section: Releasing Nutrient Elements In Insoluble Mineral Substancementioning
confidence: 99%